Financial Performance of Companies in a Stock Exchange Market - Sri Dewi Anggadini; Asep Saepudin; Nelly Armeida; Abdurrauf Umar; Sari Damayanti (Australasian Accounting Business and Finance Journal, 2024)
This study focused on the percentage of return on assets in transportation companies listed on the Indonesia Stock Exchange between 2018 and 2022 to ascertain the impact of management ownership and independent commissioners on financial performance. Purposive sampling was the sample strategy, which involved selecting 75 annual financial statements from 15 transport companies. The analytical method utilized descriptive data analysis, complementing the classic assumption test as a prerequisite assessment. This ensured that the available data met the criteria for utilizing multiple linear regression equation models. The partial test results revealed that managerial ownership positively influences financial performance, while independent commissioners also have a positive impact. This study adds to our understanding of the variables and body of literature that support an organization's financial performance as it implements multifaceted business practices that are aligned with environmental, social, and governance (ESG) principles. Moreover, it is crucial for assessing a company's performance, as evidenced by the financial statement analysis.
Keywords: Managerial; Independent Commissioner; Financial Performance